IMPROVING TENTH GRADE STUDENTS’ SPEAKING SKILL THROUGH SMALLGROUP DISCUSSION STRATEGY (SGDS) BY USING ADVERTISEMENT MATERIALS AT TAMAN SISWA VOCATIONAL SCHOOL OF PALEMBANG IN THE ACADEMIC YEAR 2019/2020 (A CLASSROOM ACTION RESEARCH) - Isna Fitriah; Tahrun Tahrun; Artanti Puspita Sari (ELTE Journal (English Languange Teaching and Education), 2020)
This research was conducted by the researcher as an English teacher at Taman Siswa Vocational School of Palembang for the tenth-grade students in the academic year of 2019/2020. Since only a few students could participate in the research, this study aimed to find out how the Small Group Discussion Strategy (SGDS) improved students' speaking skills. The subject of this study was 22 students from the tenth grade of Taman Siswa Vocational School of Palembang. The material used was advertisement materials. The materials contain selected advertisement texts to be discussed by students during the study. The method of this study was Classroom Action Research (CAR). This study was conducted in three cycles with several procedures, there were planning, implementation, observation, and reflection. Each cycle has two meetings and one test. Data from this study were obtained by using oral tests and questionnaires. The findings from this study indicated that using the Small Group Discussion Strategy (SGDS) can improve the students' speaking achievement. The improvement by improvement was seen starting from cycle II and cycle III. In Cycle II it appeared that the percentage of students who got the criteria of a minimum standard score was 68.20% and students who did not get the criteria of a minimum standard score were 31.80%. In the last cycle III. twenty students who got the criteria of a minimum standard score with a percentage of 86.40% and two students who did not get the criteria of a minimum standard score were 13.60%. This means the improvements of the tenth-grade students’ speaking skills were successful.